Successes and Challenges in Recruiting and Retaining Gang Members in Longitudinal Research: Lessons Learned From a Multisite Social Network Study - Eidson, Jillian L. (Youth violence and juvenile justice, 2017)
Members of hidden or hard-to-survey populations present challenges to social scientists seeking to engage them in empirical studies, especially if those efforts are longitudinal. In this article, we document the retention-related successes and failures of a longitudinal, social network-based study of active and desisting street gang members in Philadelphia, PA, and the District of Columbia. A purposive sample was used to identify and track 229 gang members at three points in time over 2 years to explore how the social networks of gang members change. Although gang members have many factors in common with other hidden populations, their criminal behavior and involvement with the justice system, coupled with the sensitivity of the social network survey questions for this study, created hurdles to maintaining research contact over time. With continued and systematic documentation of successes and challenges, academics can build an extensive backdrop from which to continue to study gang youth. If the field cannot devise cost-effective and transferable ways to study gangs beyond single-gang ethnographies, it will limit its understanding of important processes related to gang behavior, including gang joining and desistance.